Flood Impacts in Sprawling Landscapes: Integrating Urban Drainage, Open Spaces and Land Use in the Process of Urban Planning - Beatriz Amback; Matheus Martins de Souza; Aline Verol; Marcelo Miguez (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
Floods are strongly related to lack of proper spaces in cities. This work aims to assess the potential aggravation of floods in a sprawling area if open spaces are lost and not used in a multifunctional way to accommodate stormwaters in the urban developing process. An exploratory approach is used, focusing on a critical case study, where both environmental and social fragilities are severe. Five developing scenarios were built and simulated using a hydrodynamic tool for comparison purposes, intending to show the importance of integrating urban drainage, urban open spaces and land use and occupation planning. Results show that the tendency of worsening the situation is alarming, if no land use planning measures are taken. This study highlights the need to recognize the crucial role of open spaces in flood mitigation and to plan these spaces in advance, integrating natural water demands and ordering a safer future city occupation.